Flexor Synergy Assessment and Therapy for Persons With Stroke Using the ULIX Low Impedance Robot - Shawn J. DiRocco; Rafael Casas; Seraphina A. Culp; Peter S. Lum (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
The flexor synergy after stroke results in involuntary activation of distal muscles when lifting the shoulder against gravity. This contributes to impaired ability to perform activities of daily living. Robotic exoskeletons can be useful in assessing the strength of the synergy and applying therapy modes that promote improved movement patterns. In this study, we evaluated 16 chronic stroke patients using the Ultra Low Impedance eXoskelton (ULIX). The subjects performed two synergy assessment tasks, elbow extension and hand opening while holding shoulder flexion at greater than 70 degrees with various gravity support levels. Joints not part of the tasks were locked in place. During the assessment tasks, increasing gravity support resulted in more elbow extension and reduced grip force; however, EMG contraction ratios of distal muscles compared to deltoids increased when gravity support was increased. A free cup reaching task was performed using several proposed therapy modes. During the cup reaching task, the therapy modes increased range of motion and improved the shoulder-elbow kinematic coordination compared with gravity support alone. There was a strong correlation between synergy expression in the elbow extension task and performance of the cup reaching task. Isolating movement to shoulder flexion and elbow extension during the assessment task resulted in better elbow extension than in the cup reaching task where all joints were free to rotate.